2016
DOI: 10.1248/bpb.b15-00932
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ocular Iontophoretic Drug Transport of Ionic and Non-ionic Compounds in Isolated Rabbit Cornea and Conjunctiva

Abstract: Ocular iontophoresis (IP) in isolated rabbit cornea and conjunctiva was examined in terms of transport enhancement, tissue viability and integrity using electrophysiological parameters by the Ussing-type chamber technique. Lidocaine hydrochloride (LC, a cationic compound), sodium benzoate (BA, anionic compound), and fluorescein isothiocyanate labeled dextran (molecular weight 4400 Da, FD-4, hydrophilic large compound) were used as model permeants. Direct electric current was applied at 0.5-5.0 mA/cm 2 for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…We prepared isolated rabbit cornea and conjunctiva as previously described 14 . Rabbits were anesthetized with a 20 mg/kg sodium pentobarbital solution injected into a marginal ear vein, and euthanized using a 3.3 M KCl solution injected at the same site.…”
Section: Preparation Of Cornea and Conjunctivamentioning
confidence: 99%
See 1 more Smart Citation
“…We prepared isolated rabbit cornea and conjunctiva as previously described 14 . Rabbits were anesthetized with a 20 mg/kg sodium pentobarbital solution injected into a marginal ear vein, and euthanized using a 3.3 M KCl solution injected at the same site.…”
Section: Preparation Of Cornea and Conjunctivamentioning
confidence: 99%
“…We have previously examined drug transport through IP using viable rabbit cornea and conjunctiva 14 and found that the permeability of fluorescein isothiocyanate dextran (FD-4), a 4.4-kDa hydrophilic macromolecule, across these tissues significantly increased when the anode was placed on the drug reservoir side (anodal IP). This increase in permeability was dependent on the applied electric current density.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning iontophoresis, it is a technique that uses low currents to create transitory and localized pores in the cell membrane, allowing ionized molecules to pass through. Iontophoresis has been shown to boost gene or drug transport across the cell membrane by 2.3 and 2.5 times in the cornea and 4.0 and 3.4 times in the conjunctiva, respectively; however, after the current was removed, the transfer recovered to baseline levels in rabbit cornea and conjunctiva [86].…”
Section: Gene-based Ocular Delivery Systemsmentioning
confidence: 99%
“…A direct electrical modern-day might also be utilized to the cornea at 0.5-5.0 mA/cm2, and for the conjunctiva, it may additionally be utilized at 0.5-20 mA/cm2 for 30 min. Gene or drug travelling throughout the cell membrane by iontophoresis has been said to enlarge by means of 2.3-and 2.5-fold for the cornea and 4.0-and 3.4-fold for the conjunctiva, respectively; the switch again to baseline ranges in rabbit cornea and conjunctiva as soon as the modern-day was once no longer utilized [78]. Introducing genes and capsules into the cornea utilising contemporary is carried out by using loading the electrode with, for example, riboflavin answer and connecting it to a modern generator aiming at improving corneal crosslinking in keratoconus sufferers after epithelial debridement [79].…”
Section: Iontophoresismentioning
confidence: 99%